2021
DOI: 10.1108/ijoa-10-2019-1914
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perceived organizational support on employee performance in IT firms – a comparison among Pakistan and Saudi Arabia

Abstract: Purpose The purpose of this paper is to evaluate the influence of perceived organizational support on employees’ performance in information technology (IT) firms in Pakistan and Saudi Arabia. Organizational support is critical as it ensures support given by the organization to workers and to complete one’s job proficiently and effectively. Design/methodology/approach Data were collected from IT firm employees through a self-administered questionnaire survey where a total of 400 questionnaires were distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 90 publications
2
30
1
3
Order By: Relevance
“…From these numbers, it is fair to assert that the theory regarding the relationship between perceived organizational support and temporary staff performance has no significant effect; the assumption is not supported. The findings of this study contradict those of (Astuty & Udin, 2020;Sabir et al, 2021;Chen et al, 2020).…”
Section: Effect Of Perceived Organizational Support On the Temporary ...contrasting
confidence: 99%
See 1 more Smart Citation
“…From these numbers, it is fair to assert that the theory regarding the relationship between perceived organizational support and temporary staff performance has no significant effect; the assumption is not supported. The findings of this study contradict those of (Astuty & Udin, 2020;Sabir et al, 2021;Chen et al, 2020).…”
Section: Effect Of Perceived Organizational Support On the Temporary ...contrasting
confidence: 99%
“…In other words, it is the employee's perceptions of the quantity of support provided by the organization and the extent to which the corporation is prepared to help when needed. Employees feel supported by their companies and consider themselves part of a social exchange relationship when human resource management methods emphasize investment in employees, participative decision making, and growth possibilities (Paauwe, J., Wright, P., & Guest, 2013;Sabir et al, 2021).…”
Section: Perceived Organizational Support and Employee-organization R...mentioning
confidence: 99%
“…Organizational support is critical as it ensures support given by the organization to manage demanding conditions and to complete one's job proficiently and effectively (George, 1993). Furthermore, it is Wayne (2002) demonstrated that perceived organizational support reflects the vast degree of relationship between organization and employee (Sabir et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Organizational support theory recommends that employees create universal beliefs with regard to how much their organization owns its commitments toward objectives and goals (Eisenberger, 1986;Rhoades & Eisenberger, 2002;Shanock & Eisenberger, 2006). Because of the standard of correspondence (Sabir et al, 2022), this perceived organizational support drives employees to feel committed to showing states of mind and behaviors that will profit the organization (Wayne, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A research paper by Sabir et al (2022) explores how far perceived organizational support (POS) in employees' minds translates to employee role performance levels. The study proposes a model that's structured to help managers achieve employee performance enhancement.…”
mentioning
confidence: 99%